Development of a digital twin for demo cooling system - Mvimbi, Amandla (Department of Electrical Engineering, 2026)
CO2 - based mechanically pumped fluid systems, known as Two-phase Accumulator Controlled Loop (2PACL) systems, have continued to enjoy extensive research and exploration at CERN. The system offers operational specifications that arise as a results of the High Luminosity upgrade. These include the need to operate at a colder temperature of -45˚C at the detector and -53˚C at the pump inlet and substantially higher varying loads. Furthermore, for redundancy, the systems now need to have multiple plants in parallel. To address challenges pertaining to scaling, the systems now have novel design elements such as the addition of the surface storage, flow-through mode for the accumulator, Back Pressure Regulator, new more intricate logic. This project considers simulations that have been developed for mechanically pumped fluid systems and then develops a full-scale model for the novel 2PACL systems developed at CERN, including the new of intricate logic and functionality. The literature survey revealed that there are no simulations to conduct a system-level study or a study of this new logic. No simulations are available for the new systems with parallel architecture and new logic associated with it for smooth handover. The project further explores how the critical control loops in the new systems may benefit from a procedural control design that considers plant uncertainty and sampling effects. Simulations conducted with the model are then validated against the measurements from corresponding experiments in Demo – CERN's 2PACL prototype, which cover startup, setpoint change, load change, and the swap and re-takeover test. The results are used to validate the model fidelity – both the discrete logic and trajectory behaviour.